A historical analysis of commercial laws and health laws in pre-modern sri lanka - Wimalasena, N.A. (University of Jaffna, 2012)
Laws and Legal institutions are of vital importance for the security and progress of any society. Laws restrain members of a community from involving in crimes and acts of violence. There are prescribed punishments for offences. The present legal system consists of two parts, namely Civil Law and Criminal Law. Criminal law relates to crimes such as theft and murder. It consists of two parts, namely iniquitous and non-iniquitous crimes. Grave crimes carry the penalty of death or life-imprisonment. In the case of less serious crimes, the punishment is light. Civil Law pertains to matters relating to commerce, health, marriage, lands, property, water management, etc. In the present study, attention will be focused mainly on civil laws of pre-modern Sri Lanka with special emphasis on commercial laws and health laws. Even today, commercial law occupies a very important place in the legal system and it has many rules and regulations that are applicable for commercial activities. Similarly, In Ancient Sri Lanka, commerce was a very vital aspect among the economic activities. Some writers such as Emerson Tennent have reported that Ancient Sri Lankans were apathetic to commercial activities. However, Sri Lankan scholars researching on commerce have rejected that view. Their studies reveal that there was an internal and external trade in several commodities. Such a situation presupposes that there were very strict and comprehensive rules and regulations regarding commerce in Ancient Sri Lanka. In this paper attention will be paid to commercial rules and regulations that were formulated in ancient times. Every society has developed a system of health care and medical treatment. Presently Sri Lanka has a Department of Health services. The institutions under its management are governed by specific laws and regulations. It could be supposed that in ancient times, the island had a well-organized health system and also a hospital management system. Ancient inscriptions, literary sources and ruins of hospital buildings have confirmed it. The main objective of this study is to discern the rules and regulations relating to health and hospital management in pre-modern Sri Lankas found in ancient records. The research is mainly based on primary sources such as Pali chronicles, Commentaries and inscriptions such as the Badulla Pillar inscription, Viharahinna inscription, Lankatilake inscriptions, Kautilya Arthasastra, Mahavamsa, Medirigiriya inscription and Samantapasadika. Wherever necessary material will also be obtained from limited secondary sources on the ancient legal system of the island.